Transverse cracking in carbon fiber reinforced polymer composites: Modal acoustic emission and peak frequency analysis. (8th September 2015) - Baker, Christopher; Morscher, Gregory N.; Pujar, Vijay V.; Lemanski, Joseph R.
Abstract: The initiation and propagation of cracks in carbon-fiber reinforced toughened epoxy polymer composite laminates were studied using modal acoustic emission and waveform energies, coupled with peak frequency data and correlated to matrix crack density in the transverse direction. Composites of four different ply layups were studied. Results show the placement of the 90° ply (e.g., on the surface or internal) as well as the number of adjacent 90° plies directly influence the applied stress load at which transverse cracks are formed and the resulting stress distribution. Results for matrix cracking show that peak frequency data alone was unable to fully characterize the damage initiation, contrary to prior studies. However, based on modal acoustic emission principles, coupling the peak frequency data with acoustic energy of waveforms, effectively corresponded to the stress-dependent number of 90° ply transverse cracks and the through-the-thickness location of the 90° ply. This information can be very useful to understand stress-dependent transverse cracking in a given 90° ply or to develop optimal lay-up sequences to maximize composite properties.